Economic laws and economic history - Kindleberger, Charles Poor 1910-2003 (Raffaele Mattioli lectures, 1989)
In this volume, Charles Kindleberger makes a powerful case against the idea that any one model could be used to unlock the basic secret of economic history. It is essentially an exercise in methodology, addressed to economists and economic historians alike. He argues that too many economists discover a relationship or a uniformity in economic behaviour, develop a model, and use it to explain more than it is capable of, including, on occasion, all economic behaviour. These lectures discuss four 'laws' in economics to show how uniformities can illuminate economic history in particular aspects. They illustrate the view that the economist or economic historian seeking to test analysis against historical data should have a variety of different models, and not just one. The implication is that however scientific and technical the tools, choosing them carefully to fit particular circumstances is itself an art